“Four Environment” Method of Leading Entrepreneurship - Litau, Ekaterina (International Journal of Applied Research in Management and Economics, 2025)
In the contemporary landscape, genuine wealth stems from entrepreneurial ideas that align with moral, environmental, and economic dimensions, requiring a cohesive evaluation framework grounded in morality, science, and economic analysis. Esthetics serves as the creative bridge that balances rational and ethical principles, a dynamic exemplified by unicorn companies, whose value orientations demonstrate this interconnected approach as a key driver of global market leadership. The study examines the hypothesis by analyzing the value systems of 1,220 unicorn companies through mixed-methods research. The investigation focuses on how ethical, esthetic, and welfare considerations align with these companies' market leadership. Findings indicate a strong relationship between corporate success and adherence to universal humanistic values, fostering social development and equality. Ecological concerns occupy a significant position in these organizations' value hierarchies. The research reveals that entrepreneurs widely recognize both the imperative to generate socially impactful outcomes and the strategic importance of esthetic values in business. The study proposes the “4E Pyramid” (Economy, Ethics, Ecology, Esthetics), also termed the “Four Environment” pyramid, which represents the modern value hierarchy of unicorn companies as of November 2023. The framework demonstrates how entrepreneurial opportunities align with Maslow’s hierarchy of human needs. The findings suggest that businesses now position their activities as socially beneficial within the sustainable development paradigm while maintaining economic viability. This underscores the growing necessity of cultivating ethical and esthetic intelligence to emerge as market leaders in the evolving entrepreneurial landscape.